2012
DOI: 10.1021/jp212092h
|View full text |Cite
|
Sign up to set email alerts
|

Fast One-Step Synthesis of Biocompatible ZnO/Au Nanocomposites with Hollow Doughnut-Like and Other Controlled Morphologies

Abstract: Hollow doughnut-like ZnO/Au nanocomposites have been synthesized through a fast one-step microwaveassisted hydrothermal route. The formation mechanism of the product is closely connected with the coordination and selective adsorption effect of trisodium citrate (TSC). Other different structures, such as ZnO nanorods/Au nanoparticles, ZnO nanodisks/Au nanoparticles, and ZnO nanospheres/Au nanoparticles have also been obtained in control experiments. The UV−vis and photoluminescence properties of the asprepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 51 publications
3
36
0
Order By: Relevance
“…First, related to the doping agent, ZnO, which was not possible to detect by XRD analysis, appeared in the UV/Vis experiment. ZnO is a wideband‐gap semiconductor ( E g =3.37 eV) with a large excitation binding energy (60 meV) 15. The absorption peaked at 340 nm in the Zn/Al sample could be attributed to a well‐defined excitation band of ZnO in agreement with the absorption band observed for ZnO nanorods in Ref.…”
Section: Resultssupporting
confidence: 86%
“…First, related to the doping agent, ZnO, which was not possible to detect by XRD analysis, appeared in the UV/Vis experiment. ZnO is a wideband‐gap semiconductor ( E g =3.37 eV) with a large excitation binding energy (60 meV) 15. The absorption peaked at 340 nm in the Zn/Al sample could be attributed to a well‐defined excitation band of ZnO in agreement with the absorption band observed for ZnO nanorods in Ref.…”
Section: Resultssupporting
confidence: 86%
“…It can be concluded that the plates are highly (001) facet exposed, which is consistent with its highest intensity of (001) peak among three samples in Figure 1. As reported previously [24][25][26], the selective combination of citrate with (001) facet of ZnO resulted in the final (001) exposed structures, which was supported by the complexation between carboxyl and zinc atoms. In this experiment, ZnO-NC showed rod-like shape while ZnO-OS were plate-like (Figure 2a,c), confirming that citrates are effective for ZnO shape controlling.…”
Section: Resultssupporting
confidence: 77%
“…A previous study demonstrated that the crystallinity of Au seeds controlled the nucleation process [33,34]. Similarly, it is reasonable that the morphology of Au@TiO2 was controlled by the contents of Au in this study.…”
Section: Structural and Morphological Characteristicssupporting
confidence: 77%